KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS MALARIA TEST AND TREATMENT POLICY AMONG HEALTH WORKERS IN KAPCHORWA GENERAL HOSPITAL, KAPCHORWA DISTRICT. A CROSS-SECTIONAL STUDY. - CHELANGAT, VIOLET; Tushaba , Ohurira (Student's Journal of Health Research Africa, 2023)
The purpose of the study. The purpose of the study was to assess the knowledge, attitude, and practices towards malaria test and treatment policy among health workers in Kapchorwa Hospital, Kapchorwa district. Objectives of the study The specific objectives of the study were; to assess the knowledge of malaria test and treatment policies among health workers, to determine the attitude towards malaria test and treatment policies among health workers, and to determine practices towards malaria test and treatment policies among health workers in Kapchorwa hospital, Kapchorwa district. Methodology. The study design employed was a descriptive cross-sectional, to address the specific objectives of the study on a sample of 50 respondents using simple random sampling techniques. Some structured questionnaires were designed and used as a data collection tool. Results of the study. From the study findings, the majority of the respondents (64%) have never heard about the WHO malaria test and treatment policy, (70%) of the respondents have received training on the malaria test and treatment, (46%) of the respondents knew about microscopic malaria testing, 80% of the respondents agreed with the malaria test and treat policy,100% felt it should be implemented,70% said MTTP increased health workers’ perception. Conclusion. In conclusion, the overall knowledge of the respondents of malaria was not pleasing though their attitude was pleasing when the majority of them agreed to do malaria testing before treatment as well with their practices were pleasing were majority reported to do malaria testing before treatment. Recommendation. The Ministry of Health should intensify the supervision of health workers to adhere to the malaria test and treatment policy and also carry out further training of health workers in Kapchorwa Hospital to improve their knowledge of the malaria treatment policy.